Perceived Impact of Stress on Academic Performance among Students of Aliko Dangote College of Nursing Sciences Bauchi, Bauchi State - Maimuna, Muhammad; Musa, Muhammad Maryam; Salisu, Umar Muhammad; Dambam, Muhammad Fatima (THRIVE Health Science Journal, 2026)
Stress has been tagged as a global phenomenon. It has become an integral part of life and is said to be the price that all human beings pay for the struggle to stay alive. Stress is a particularly important issue in education because it has the potential to impede concentration, memory, and problem-solving ability, which in turn adversely affect academic performance and learning. Stress refers to a dynamic interaction between the individual and the environment. The study was conducted on Perceived impact of stress on academic performance among students of Aliko Dangote College of nursing sciences Bauchi. The objective of the study was to assess the perception of stress among students of Aliko Dangote College of nursing sciences Bauchi. A descriptive cross sectional research design was used, using self-administered questionnaire. Proportionate Stratified Random sampling technique was used to select a total 308 of participants. Data was analyzed and presented in frequency table and mean. Heavy academic work load, period of examination, fear of examination failure were accepted by the respondent as the common sources of stress among students. Students of Aliko Dangote College of nursing sciences perceived stress as a source of anxiety and negatively affect academic performance, students adopt various coping mechanisms which include, meditation, exercises like deep breathing or yoga, having good social relationship with friend. In recommendation there is a need for the college of nursing sciences department of nursing Aliko Dangote Bauchi and any other management involved to restructure academic schedules that can lessen the burden responsible for stress among students, school management should also give attention to stressors in the workplace and how these contribute to student stress.